Pengaruh Beban Kerja Dan Burnout Terhadap Kinerja Karyawan Pada Pt Maju Gemilang Persada Jakarta Barat - Meisya Wulandari; Hira Maulida (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract - This study aims to determine the influence of workload and burnout on employee performance at PT. Maju Gemilang Persada both partially and simultaneously. The type of research used is quantitative with data analysis methods used in this study are validity test, reliability test, classical assumption test, quantitative analysis, regression analysis, and hypothesis test. The population in this study were employees of PT. Maju Gemilang Persada totaling 56 respondents. The results of this study indicate that the influence of workload variables on employee performance from the results of the t test, sig. value. = 0.001 <0.05 and t count (5.376) > (1.984) t table, the influence of burnout on employee performance from the results of the t test, sig. value. = 0.001 < 0.05 and t count (7.893) > (1.984) t table, and the effect of workload and burnout on employee performance from the calculated f value of 30.655 > f table 3.17, from all these variables means H0 is rejected and Ha is accepted. Thus, it can be concluded that workload and burnout partially and simultaneously have a positive and significant influence on employee performance at PT. Maju Gemilang Persada.